Digitalization Of Zakat Through Innovation In Sharia Financial Technology As A Form Of Fiscal Transformation Islamic At Baznas - Yuana, Anik Gita; Nindyah Siska Handayani; Sri Utami (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2025)
This study aims to analyze the implementation of zakat digitalization through Islamic financial technology innovation as a form of Islamic fiscal transformation at the National Zakat Agency (BAZNAS). Using a descriptive qualitative approach, data were collected through in-depth interviews with BAZNAS leaders, staff, as well as zakat payers (muzakki) and recipients (mustahiygk) involved in the digital zakat system. The results reveal that digital zakat platforms, the BAZNAS Management Information System (SIMBA), and the integration of Syariah QRIS have significantly enhanced the efficiency, transparency, and accountability of zakat fund management. Moreover, the utilization of Islamic fintech has strengthened public trust and positioned zakat as an essential fiscal instrument promoting justice and equitable economic distribution. However, several challenges remain, including low digital literacy, data security concerns, and limited human resource competence in technology management. Strengthening institutional capacity, crosssector collaboration, and digital education are crucial strategies to optimize this transformation. Hence, BAZNAS has the potential to become a national model for sustainable and equitable Islamic fiscal transformation driven by technology.